The Potential of Government Intervention in Violence Against Women: Lessons from Newfoundland and Labrador - Manning, Susan M. (Atlantis, 2015)
While an increasingly neoliberal and neoconservative state has created challenges for Canadian feminists, Newfoundland and Labrador’s Purple Ribbon Campaign, launched in 2009, illustrates how feminist analyses of gender-based violence can be incorporated into a government-sponsored anti-violence campaign. This article examines the successes and limitations of the Purple Ribbon Campaign’s anti-violence analyses.